Associations of propylene oxide exposure with fasting plasma glucose and diabetes: Roles of oxidative DNA damage and lipid peroxidation. (1st January 2022) - Liu, Wei; Wang, Bin; Yang, Shijie; Xu, Tao; Yu, Linling; Wang, Xing; Cheng, Man; Zhou, Min; Chen, Weihong
Abstract: Whether propylene oxide (PO) exposure is associated with hyperglycemia were rarely explored. We aimed to determine the relationship between PO exposure and glucose metabolism, and potential role of oxidative stress. Among 3294 Chinese urban adults, urinary PO metabolite (N-Acetyl-S-(2-hydroxypropyl)-L-cysteine, 2HPMA), biomarkers of oxidative DNA damage (8-oxo-7, 8-dihydro-20-deoxyguanosine, 8-OHdG) and lipid peroxidation (8-isoprostane, 8-iso-PGF2α ) in urine were determined. The associations of 2HPMA with 8-OHdG, 8-iso-PGF2α, fasting plasma glucose (FPG), and risk of diabetes were explored. The roles of 8-OHdG and 8-iso-PGF2α on association of 2HPMA with FPG and risk of diabetes were detected. After adjusted for potential confounders, each 1-unit increase in log-transformed concentration of 2HPMA was associated with a 0.15-mmol/L increase in FPG level, and the adjusted OR (95% CI ) of diabetes by the associations of log-transformed urinary 2HPMA concentrations was 1.47 (95% CI : 1.03–2.11). Combination effects of 2HPMA with 8-OHdG or 8-iso-PGF2α on risk of diabetes were detected, and elevated 8-iso-PGF2α significantly mediated 34.5% of the urinary 2HPMA-associated FPG elevation. PO exposure was positively associated with FPG levels and risk of diabetes. PO exposure combined with DNA oxidative damage or lipid peroxidation may increase the risk of diabetes, and lipid peroxidation may partially mediate the PO exposure-induced FPG elevation. Graphical abstract: Image 1 Highlights: Individual PO internal exposure was evaluated in general population. PO was significantly associated with FPG and risk of diabetes. Both 8-OHdG and 8-iso-PGF2α combined with PO exposure increased diabetes risk. 8-iso-PGF2α might mediate the association between PO exposure and FPG elevation.